Povezanost vrednot v tenisu in smučarskih skokih - Filipič-Jeras, Ksenija (Šport (Ljubljana), 2022)
The purpose of the research was to determine the connection between the values of ski jumpers and female players and tennis players. Based on a written questionnaire, 134 ski jumpers between the ages of 12 and 28 and 75 tennis players of both sexes, men aged 13 to 44 and women aged 13 to 24, were included in the research. We used Likert-type rating scales with ratings from 1 to 5, the obtained data were processed with the SPSS statistical package. The correlation between values in tennis and ski jumping was high (r = .90) and statistically significant (p<0.01). The magnitude of the rank correlation coefficient was hypothetically unexpected, since ski jumping and tennis are quite different from each other in terms of the nature of the sports activity. Respondents in tennis rated the statement „I like to win“ the highest, which belongs to the Dionysian values of the power type. The ski jumpers rated this claim above average (4.2), but it was ranked only in eighth place. The results of the research showed that the values of sport are more important to ski jumpers, which according to Musk (2000) belong to the Apollonian type values associated with dominant intrinsic motivation.
Keywords: povezanost; smučarski skoki; šport; športniki; tenis; vrednote